×2 - 2 × + 4 , p/ × = -2
Soluções para a tarefa
Respondido por
4
x² - 2 x + 4 x = - 2
( - 2 )² - 2 . ( - 2 ) + 4
4 + 4 + 4
12
( - 2 )² - 2 . ( - 2 ) + 4
4 + 4 + 4
12
Respondido por
1
x² - 2x + 4
Para x = -2
===
Substituir o valor dado para x na expressão:
x² - 2x + 4
(-2)² - 2.(-2) + 4
4 + 4 + 4
=> 12
Para x = -2
===
Substituir o valor dado para x na expressão:
x² - 2x + 4
(-2)² - 2.(-2) + 4
4 + 4 + 4
=> 12
Perguntas interessantes
Sociologia,
11 meses atrás
Matemática,
11 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Administração,
1 ano atrás